Type 1 Diabetes & Schools: Parents Experiences - Haegele, Justin A.; Holland, Steven K.; Hill, Edward; Ramsing, Ron (International Journal about Parents in Education, 2025)
The purpose of this study was to explore the experiences, and meaning ascribed to those experiences, of parents of children with type 1 diabetes (T1D) in U.S. school settings. Twenty-nine parents (19 mothers and 10 fathers) participated, and four sources of data were collected for this interpretivist, phenomenological study; a demographic questionnaire, written prompt, semi-structured focus group interviews, and reflective interview notes. Three themes were constructed: (a) I’m fighting for my child, (b) nurses are central to experiences, and (c) physical education problems. The findings highlighted parents’ frustrations with resistant schools and the need to be advocates for their child’s needs while also emphasizing the importance of an available, and T1D-competent, nursing staff in reducing fear and anxiety associated with in-school care. Uniquely, parents discussed contextual experiences and how experiences changed throughout the day with particular emphasis on the problematic and negative experiences associated with physical education.